2023
DOI: 10.31616/asj.2022.0320
|View full text |Cite
|
Sign up to set email alerts
|

Patient Positioning in Spine Surgery: What Spine Surgeons Should Know?

Abstract: Spine surgery has advanced tremendously over the last decade. The number of spine surgeries performed each year has also been increasing constantly. Unfortunately, the reporting of position-related complications in spine surgery has also been steadily increasing. These complications not only result in significant morbidity for the patient but also raises the risk of litigation for the surgical and anesthetic teams. Fortunately, most position-related complications are avoidable with basic positioning knowledge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…A study by Kamel et al 75 identified significant changes in somatosensory evoked potential with the prone-superman comparted to the prone, arms tucked positions. Factors such as excessive elbow flexion (>90°), direct compression of the cubital tunnel, the arm migrating during surgery and obesity are known risk factors [76][77][78] . Traction neuropraxias and compression induced ischemic injuries of the brachial plexus occur due to mal-positioning in prone.…”
Section: Specific Problems In Spinal Surgery: Managing the Prone Patientmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Kamel et al 75 identified significant changes in somatosensory evoked potential with the prone-superman comparted to the prone, arms tucked positions. Factors such as excessive elbow flexion (>90°), direct compression of the cubital tunnel, the arm migrating during surgery and obesity are known risk factors [76][77][78] . Traction neuropraxias and compression induced ischemic injuries of the brachial plexus occur due to mal-positioning in prone.…”
Section: Specific Problems In Spinal Surgery: Managing the Prone Patientmentioning
confidence: 99%
“…Traction neuropraxias and compression induced ischemic injuries of the brachial plexus occur due to mal-positioning in prone. Excessive arm abduction (>90) hypovolaemia, hypothermia, a history of alcohol dependency and diabetes mellitus are all risk factors 76 . Finally, LFCN injury has a reported incidence of 10%-24% during posterior spine surgery 79 , with compression at the anterior superior iliac spine the most prevalent cause, for example by supports or bolsters.…”
Section: Specific Problems In Spinal Surgery: Managing the Prone Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…We were intrigued by the article by Garg et al [ 1 ], which discussed position-related complications associated with the prone position. However, we still have some concerns about the article.…”
mentioning
confidence: 99%
“…We thank the authors for their interest in our article [ 1 ] and kind words of appreciation. The point wise reply for the concerns raised is as follows:…”
mentioning
confidence: 99%